Does technology improve reading outcomes? Comparing the effectiveness and cost-effectiveness of ICT interventions for early grade reading in Kenya. (July 2016) - Piper, Benjamin; Zuilkowski, Stephanie Simmons; Kwayumba, Dunston; Strigel, Carmen
Highlights: Policymakers in Sub-Saharan Africa are increasing investments in ICT without evidence of the impact of different ICT options on learning outcomes. The PRIMR program showed that three interventions had significant impacts on learning outcomes in English and Kiswahili. PRIMR's results using ICT are not significantly different from the effects identified from the non-ICT base PRIMR program. The costs of ICT differ greatly and therefore the cost-effectiveness of ICT varies significantly. Abstract: Education policymakers are investing in information and communications technology (ICT) without a research base on how ICT improves outcomes. There is limited research on the effects of different types of ICT investments on outcomes. The Kenya Primary Math and Reading (PRIMR) study implemented a randomized controlled trial comparing the effects and cost of three interventions – e-readers for students, tablets for teachers, and the base PRIMR program with tablets for instructional supervisors. The results show that the ICT investments do not improve literacy outcomes significantly more than the base non-ICT instructional program. Our findings show that cost considerations should be paramount in selecting ICT investments in the education sector.